2009
DOI: 10.1177/000313480907500414
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of the Colon: A Rare Cause of Colovesical Fistula

Abstract: Carcinosarcomas are relatively rare tumors composed of both carcinomatous and sarcomatous components. The most common sites involved by this tumor are the head and neck, respiratory tract, uterus, ovaries, and fallopian tubes. Within the gastrointestinal tract this tumor most often occurs in the esophagus, followed by the stomach. Carcinosarcomas are very aggressive tumors associated with a poor prognosis. The first case of carcinosarcoma of the colon was reported in 1986. The case reported here is the only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…Advanced-stage colon and bladder malignancies account for up to one-fifth of all cases, with the latter being extremely rare [ 4 , 15 ]. Other urogenital malignancies, as well as lymphoma, cause EVF only occasionally [ 16 , 17 ]. The iatrogenic aetiology of enterovesical fistulae may occur as a consequence of general surgical procedures (particularly for colorectal cancer, diverticulitis, or inflammatory bowel disease), as well as vascular and urological interventions [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Advanced-stage colon and bladder malignancies account for up to one-fifth of all cases, with the latter being extremely rare [ 4 , 15 ]. Other urogenital malignancies, as well as lymphoma, cause EVF only occasionally [ 16 , 17 ]. The iatrogenic aetiology of enterovesical fistulae may occur as a consequence of general surgical procedures (particularly for colorectal cancer, diverticulitis, or inflammatory bowel disease), as well as vascular and urological interventions [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Colorectal carcinosarcoma is an extremely rare entity. The first reported case dates back to 1986 by Weidner and Zekan [8], and since then, 31 cases have been reported till date (Table 1) [9, 12-15, 18, 19, 21-25, 30-32, 35-37]. Reviewing the characteristics of the reported cases in the medical literature (Table 2) revealed that the mean age of presentation is 64 years with a range between 13 and 86 years, a male to female ratio of 13:18 with 42% of reported cases being male and 58% females.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes it arises in the gastrointestinal tract, predominantly in the esophagus or the stomach [ 2 , 3 ]. Colonic sarcomatoid carcinomas are rare tumors, with 22 cases documented either as sarcomatoid carcinomas or carcinosarcomas in the literature [ 4 - 25 ]. This tumor is generally aggressive with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%